Innovation of The SIMPARI Application (Tax Collection Monitoring Management System for PBB - P2 and PBHTB in Wonosari District) to Improve Land and Building Taxes in Bondowoso Regency - Honest Dody Molasy; Nova El Maidah; Sus Eko Zuhri Ernada; M. Rayhan Hanif; Anisa Kirana Damayanti; Nadira Fri Damayanti; Bellinda Aliefia Diardi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Taxes are one of the main sources of state revenue to support development and public services. However, cases of tax abuse in Bondowoso are still common. To address this issue, the SIMPARI application was developed to improve transparency, efficiency, and accountability in tax collection in Wonosari District, Bondowoso Regency. This activity aims to improve transparency, efficiency, and accountability in tax collection through a technology-based application and to provide adaptive technological solutions for areas with limited internet access. The community service activity was carried out using a Participatory Action Research (PAR) approach, which was analyzed using descriptive qualitative methods, by maximizing Focus Group Discussions (FGD) with the target group of the activity, namely 75 tax collectors in Wonosari District and 75 community respondents or taxpayers. The results of the community empowerment activities show that the SIMPARI application can be used and utilized by tax officers and the community. In addition, the impact of the activities shows that the community and tax officers also have a high level of satisfaction after the implementation of the SIMPARI application and are committed to using the SIMPARI application as a process for collecting and monitoring PBB-P2 and PBHTB taxes.